The effect of good corporate governance, firm size, leverage and profitability on accounting conservatism level in banking industry - Dianita Affianti; Supriyati Supriyati (Universitas Hayam Wuruk Perbanas, 2017)
This study aims to examine the effect of good corporate governance, firm size, leverage, and profitability on accounting conservatism level. The population used in this study is all banking industry companies, listed on the Indonesia Stock Exchange (BEI) 2008-2015, which present good corporate governance reports completely. The sampling technique used in this research is purposive sampling method. There are 18 companies qualified as the research sample. Data analysis method used is multiple linier regres-sion analysis using SPSS 23 for Windows program, with the significance level used is 0.05. The results show that good corporate governance and firm size have no signifi-cant effect on accounting conservatism level, while leverage and profitability have significant effect on accounting conservatism level.